The Importance of Developing Mathematical Literacy to Improve Students’ Critical Thinking Abilities - Safitri, Nadya (EDUCTUM: Journal Research, 2023)
Mathematical literacy is the ability to formulate, use and interpret mathematics in various contexts of daily life problems. Mathematical literacy skills are not only about basic algorithms, formulas, procedures or conventions but are also expected to be able to analyze, think critically and reason, and communicate ideas and be able to solve problems so that they can make life easier. Based on PISA 2015, students’ abilities in mathematics in Indonesia are still low compared to other countries. Teachers as educators must instill a positive perception of mathematics in students. For this reason, teachers are required to innovate mathematics learning by choosing learning methods that suit the material and student characteristics so that it will increase student motivation. With such efforts, students will improve their critical thinking skills.